1995
DOI: 10.1111/j.1365-2826.1995.tb00802.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that Melatonin Acts in the Pituitary Gland through a Dopamine‐independent Mechanism to Mediate Effects of Daylength on the Secretion of Prolactin in the Ram

Abstract: A previous study provided evidence that melatonin acts in the pituitary gland to mediate the effects of daylength on the secretion of prolactin in sheep. This was based on the observation that hypothalamo-pituitary disconnected (HPD) Soay rams showed normal patterns in the changes in the peripheral blood concentrations of prolactin in response to alterations in photoperiod (10-fold higher concentrations under long than short days), and in response to exogenous melatonin (rapid decline following the administrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
2

Year Published

1998
1998
2013
2013

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(50 citation statements)
references
References 30 publications
(41 reference statements)
1
47
2
Order By: Relevance
“…Strong evidence shows that the melatonin duration signal does not target the PD [59] or hypothalamic factors such as dopamine [60,61] to regulate the seasonal PRL rhythm. Indeed the PT is the major tissue target in this process (reviewed in [56,62]) (fig.…”
Section: Pt a Melatonin Target Tissue To Control Photoperiodic Respomentioning
confidence: 99%
“…Strong evidence shows that the melatonin duration signal does not target the PD [59] or hypothalamic factors such as dopamine [60,61] to regulate the seasonal PRL rhythm. Indeed the PT is the major tissue target in this process (reviewed in [56,62]) (fig.…”
Section: Pt a Melatonin Target Tissue To Control Photoperiodic Respomentioning
confidence: 99%
“…Sheep milk production is a direct reflection of reproductive periodicity. Prolactin, which is probably the most important hormone controlling milk production, shows a seasonal variation throughout the year, associated with daylength changes (Thimonier et al, 1978), and it has been demonstrated that the seasonal rhythm of prolactin secretion is under pineal control by the secretion of melatonin (Reiter, 1991), which exerts a suppressive effect on prolactin (Lincoln and Clarke, 1995). Altered photoperiod influences milk production in dairy cattle, but evidence for this relationship in sheep is scarce.…”
Section: Introductionmentioning
confidence: 99%
“…Chronic administration of exogenous melatonin during long days shapes the secretion of the above-mentioned hormones in a similar manner [4, 5, 6]. Such response to the melatonin signal requires however long-term actions of the amine on the hypothalamus [6, 7]or on the pituitary gland [8, 9]. The mechanism of this action is still under investigation.…”
Section: Introductionmentioning
confidence: 99%